The Role of Social Media in Political Mobilization: A Study of APC Gubernatorial Election in Gombe State - Mohammed, Mamud Yero; Kirfi, Musa Mohammed (Kashere Journal of Politics and International Relations, 2024)
The study seeks to examine the role of social media in political mobilization of APC Gubernatorial Election in Gombe State (2019-2023). Four research objectives were formulated that guides the study which are; the role social media played in political mobilization, the impact social media played in the political mobilization, how political mobilization is enhance via the use of social media and solutions to the challenges faced by use of social media in political mobilization of APC gubernatorial election in Gombe State. Descriptive survey design was employed in the study. The population of the study will constitute the entire population of Gombe state of 2,365,040 according to 2006 census. Sample size of 400 social mobilizers of APC Gubernatorial Election in Gombe State was used as sample for the study. Questionnaire was used as instrument for data collection. The data collected were analyzed using Statistical Package for Social Science. The results revealed that mobilization through Facebook invites more people to the party, social media posts on a Facebook encourage political mobilization and posting on Facebook motivates people to get interest on the party during APC gubernatorial election in Gombe State. The study also concludes that advertisement of contestant on Instagram through the use of videos, reduce the rate of protest and play major role in political mobilization of APC gubernatorial election in Gombe State. The study recommended that Facebook should be used as effective tool for social media mobilization of political activities.